Shock séptico - Pacheco, José (2015)
The shock is a condition that causes inadequate perfusion of oxygenated blood to the cellular level. Recalling that the perfusion depends on three components, or the circulating blood volume, vascular channels and heart pump or other active components, the shock may occur when any of these components is affected. The shock caused by bacterial toxins resulting in disorders in which arterioles occurs, though not invariably, vasodilation.